Taxation of the rich and incentives for investments: The case of Norway - Geir H. M. Bjertnæs (Statistics Norway, Research Department, 2023)
Taxation of capital income and wealth redistributes from the rich but may harm the Norwegian economy as business investments is distorted. This study shows how to redistribute from the richest without distorting investment decisions of foreign and domestic investors within a simplified model framework designed for modest levels of taxes on capital income and wealth. A wealth tax without a discount for working capital combined with a tax rate on ordinary income equal to the corporate tax rate abroad achieves these goals. This tax proposal is assessed based on previous results on taxation.
Keywords: H2; H21; F21; 330; Taxation; capital income; wealth